What are the principles of legitimacy and licitly and their resources - حسين, محمد طه (Journal of Legal Sciences, 2019)
One of the priorities of having a constitutional life is the establishment of a state of law. This is what gives the constitution credibility and realism, and gives the constitutional judiciary a real ability to perform its function in ensuring respect for the constitution and not exceeding it. Therefore, every state should strive to achieve its legality. A number of principles, principles and rules, including the commitment to the principles of legality and legitimacy, and the first concerns the public bodies in terms of composition and terms of reference, with respect to the second work issued by, and each of The two elements of its existence depends on them, and the sources of both principles must be derived and then stop them, and all this Sndersh in our research.